2018
DOI: 10.1111/nph.15570
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungi increase grain yields: a meta‐analysis

Abstract: Increasing grain yields of food cereal crops is a major goal in future sustainable agriculture. We quantitatively analyzed the potential role of arbuscular mycorrhizal (AM) fungi in enhancing grain yields of seven cereal crops with exceptional importance for human nutrition across the globe: corn, wheat, rice, barley, sorghum, millet and oat.We conducted a meta-analysis for three datasets including both English and Chinese language publications: the 'whole' dataset including both laboratory and field studies (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
157
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 243 publications
(175 citation statements)
references
References 60 publications
(82 reference statements)
17
157
1
Order By: Relevance
“…It has been known that cultivars of wheat exhibit different responses to mycorrhizal fungal inoculation [11,12,19,20]. Although earlier studies found that older cultivars strongly responded to AM fungal inoculation, later studies provide mixed results [16,18,21]. This study found some support for older cultivar responding differently than recent cultivars.…”
Section: Plos Onementioning
confidence: 48%
See 2 more Smart Citations
“…It has been known that cultivars of wheat exhibit different responses to mycorrhizal fungal inoculation [11,12,19,20]. Although earlier studies found that older cultivars strongly responded to AM fungal inoculation, later studies provide mixed results [16,18,21]. This study found some support for older cultivar responding differently than recent cultivars.…”
Section: Plos Onementioning
confidence: 48%
“…A meta-analysis [21] showed no evidence that new wheat genotypes have lost their ability to respond to mycorrhizal fungi. On the other hand, a recent meta-analysis by Zhang et al [16] showed that there is a tendency of newer wheat varieties showing decreased response to AM fungi in terms of yield.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the frequent demonstration of efficacy in laboratory and greenhouse experiments, the inconsistency of effectiveness or the lack of field data regarding AM fungi inoculation is still one of the main restraints for its wide application [22,50,51]. According to the meta-analysis of Zhang et al [52] there is a bias favoring controlled conditions for AM fungi inoculation; laboratory studies including inoculated crops tend to lead to higher grain yield increase in comparison with those studies carried out in the field. Surprisingly, our work contrasts these data as it shows that the positive effect of multiple AM fungi inoculation is maximized under field conditions.…”
Section: Discussionmentioning
confidence: 99%
“… The unprecedented challenge to feed the rapidly growing human population can only be achieved with major changes in how we combine technology with agronomy 1 . Despite their potential few beneficial microbes have truly been demonstrated to significantly increase productivity of globally important crops in real farming conditions 2,3 . The way microbes are employed has largely ignored the successes of crop breeding where naturally occurring intraspecific variation of plants has been used to increase yields.…”
mentioning
confidence: 99%